PECULIARITIES OF FLORISTIC COMPOSITION OF THE FIRST POPULATION OF THE ENDEMIC SPECIES ROSA DSHARKENTI CHRSHAN. IN THE LOWER REACHES OF THE USEK RIVER (Experimental biology, 2026)
The study is devoted to the floristic and geobotanical analysis of plant communities involving the rare endemic species Rosa dsharkenti Chrshan., localized in the valley of the Usek River, in the area of the low mountain massif “Kyzyl Espe”, located in the southern part of the Dzungarian Alatau. The relevance of the work is determined by the restricted distribution range of this species, the insufficient study of its habitats, and the need to clarify the floristic features of the plant communities in which it occurs.During the study, the species composition of plants growing together with Rosa dsharkenti Chrshan. was examined, and their life forms, ecological types,  economically useful groups, and geographical elements of the flora were determined. Based on the floristic analysis, a complete list of plant species occurring together with this species is presented, which makes it possible to characterize the structure and features of the vegetation ...
Keywords: Rosa dsharkenti Chrshan., floristic composition, geobotanical description, endemic species, Usek River valley, Dzungarian Alatau